Route planning in small medium-size companies: an integrated and sustainable approach - Costa, Diogo (2022)
Companies operating in the sector of transportation have faced the challenge of transporting productsin a high level of service and, at the same time, consider aspects related to sustainability, as the reduction of CO2, for example. In companies operating in this sector, the demand for transporting goods involves a strict control around compliance by the consumers, moreover, the need to increase quality and reduce costs when transporting goods has been one of the major concerns. Aiming to solve this challenge, logistics aspects can be considered as an important tool to support companies on developing the processes of transportation in an effective and efficient way. In this context, this research aims to understand how to bridge this gap, when analyzing the planning and management of routes in a SME in a sustainable manner, focusing on a flower company, and then to identify the problems related to distribution of products. The obtained results summarize the main problems related to distribution routes of the company, and a proposal to face those problems considering sustainable aspects was listed. For instance, solutions, such as introduction of the coordinates of all customers in the PHC software, design of new distribution zones, and a proposal to control the routes through a software with the new distribution zones for the optimization of routes. Altogether, it allowed the company to reduce the time to perform this task, as well to reduce the CO2 emission during the transportation.